Manajemen Peningkatan Mutu Dosen Pendidikan Tinggi Keagamaan Islam Swasta di Jawa Barat (Studi Kasus di STAIPI Bandung - Usep Dedi Rostandi (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
This research is motivated by the low quality of lecturers at the Private Islamic Religious Higher Education (PTKIS). The low quality of the lecturers, among others, can be seen from the accreditation of study programs and accreditation of institutions within the PTKIS scope, the low results of research and community service, the low functional positions of lecturers, etc. The general objective of this research is how to improve the management of the quality of private Islamic higher education lecturers, especially Sekolah Tinggi Agama Islam Persis Bandung. This study uses a qualitative approach with analytical descriptive methods. The data source of this research was obtained based on the results of interviews, observation, and documentation study. The results showed that the improvement of the quality of lecturers at Sekolah Tinggi Agama Islam Persis Bandung has been implemented but has not yet had an optimal impact. This can be seen from the low impact of the lecturer quality improvement program, both from education, research, and community service. Public. Improving the quality of lecturers is still constrained by internal and external constraints. Internal constraints are the low level of understanding, skills, and motivation to improve the lecturers themselves because the lecturer paradigm has not changed as an educator whose main task is only as a teacher. Internal constraints are also indicated by the low academic functional position of Sekolah Tinggi Agama Islam Persis Bandung lecturers and the lack of leadership supervision to improve the quality of lecturers. Meanwhile, external obstacles include the lack of information on improving the quality of lecturers obtained from the Ministry of Religion and other parties and the lack of optimal training of lecturers from Kopertais.